Two‐year Follow‐up of a Pragmatic Randomised Controlled Trial Examining the Effect of Adding a Carer's Skill Training Intervention in Inpatients with Anorexia Nervosa. (23rd December 2015) - Magill, Nicholas; Rhind, Charlotte; Hibbs, Rebecca; Goddard, Elizabeth; Macdonald, Pamela; Arcelus, Jon; Morgan, John; Beecham, Jennifer; Schmidt, Ulrike; Landau, Sabine; Treasure, Janet
Abstract: Background: Active family engagement improves outcomes from adolescent inpatient care, but the impact on adult anorexia nervosa is uncertain. Aim: The aim of this study was to describe the 2‐year outcome following a pragmatic randomised controlled trial in which a skill training intervention (Experienced Caregivers Helping Others) for carers was added to inpatient care. Method: Patient, caregiver and service outcomes were measured for 2 years following discharge from the index inpatient admission. Results: There were small‐sized/moderate‐sized effects and consistent improvements in all outcomes from both patients and carers in the Experienced Caregivers Helping Others group over 2 years. The marked change in body mass index and carers' time caregiving following inpatient care was sustained. Approximately 20% of cases had further periods of inpatient care. Conclusion: In this predominately adult anorexia nervosa sample, enabling carers to provide active support and management skills may improve the benefits in all symptom domains that gradually follow from a period of inpatient care. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.